Sustainable Development Goals, Extractives Industries and the Energy Nexus – Insights in the Middle East and North Africa (MENA) Region - Kilani, John (Journal of Sustainable Development Law and Policy, 2025)
Sustainable development is undoubtedly one of the biggest challenges the world continues to face today. We live in a world where more than 800 million people still live in extreme poverty; one out of nine people are starving; 2.5 billion lack access to clean water; and 1.3 billion people have no access to modern electricity. It is against this backdrop that the world leaders in September 2015 adopted the 2030 Agenda for Sustainable Development, enshrining the 17 UN Sustainable Development Goals (SDGs) – a new, universal set of goals, targets and indicators that all UN Member States are expected to use for framing their sustainable development agendas and policies until 2030. This article seizes the opportunity to engage in the ongoing discourse on the contributions from major sectors to the realization of the SDGs, particularly in the face of growing world population. The purpose of the article is to explore the role of the energy sector in the implementation of sustainable development agendas, particularly in the MENA region. The article finds that the region’s diverse circumstances and substantial petroleum and natural gas reserves make it an ideal region for typifying the central role of energy in today’s world. The article explores, under five themes, some pertinent issues relating to the UNSDGs and their connectivity to energy, drawing illustrative examples from four countries – one small resource rich country (Qatar), one relatively large resource-rich country (Saudi Arabia), the largest country from North Africa (Egypt), and a country grappling with the challenges of reconstruction after years of strive and instability (Iraq). The article highlights that some of the countries are successfully unlocking the benefits of economic growth, through the development of their natural resources. It concludes that, through concerted efforts to address some challenges, extractive sector operations can play significant roles in advancing the SDGs in the entire region.